Growth and properties of strained VO x thin films with controlled stoichiometry - Rata, Diana; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2004)
We have succeeded in growing epitaxial films of rocksalt VOx on MgO(001) substrates. The oxygen content as a function of oxygen flux was determined using 18O2-Rutherford backscattering spectrometry and the vanadium valence using x-ray-absorption spectroscopy. The upper and lower stoichiometry limits found are similar to those known for bulk material (0.8<x<1.3). From the reflection high-energy electron diffraction oscillation period a large number of vacancies for both vanadium and oxygen were deduced, i.e., ≈16% for stoichiometric VO. These numbers are, surprisingly, very similar to those for bulk material and consequently quite strain insensitive. X-ray-absorption spectroscopy measurements reveal that the vacancies give rise to strong non-cubic crystal field effects. The electrical conductivity of the films is much lower than the conductivity of bulk samples, which we attribute to a decrease in the direct overlap between t2g orbitals in the coherently strained layers. The temperature dependence of the conductivity is consistent with a variable range hopping mechanism.